AB0202 GENETIC SUSCEPTIBILITY AND PHENOTYPE OF RHEUMATOID ARTHRITIS IN DANISH AND TURKISH PATIENTS. (2nd June 2020) - Lauridsen, K. B.; Linauskas, A.; Rasmussen, C.; Can, G.; Onen, F.; Dreyer, L.; Steffensen, R.; Nielsen, K. R.; Steen Krogh, N.; Akar, S.; Akkoc, N.
Abstract : Background: Previous studies indicate that genetic susceptibility and phenotype of rheumatoid arthritis (RA) differ between the populations. Objectives: To compare the clinical, serologic expression and the presence of shared epitopes (SE) of incident RA in two different populations, one from Northern and the other from Southern Europe. Methods: Data on incident RA patients fulfilling EULAR/ACR 2010 classifications criteria for RA were collected at Rheumatology Departments in Denmark and Turkey in 2015-2016. Patients were assessed using the same standardized protocol in both populations. SE carrier status were assigned, according to the du Montcel classification based, into six allele groups: S1, S2, S3D, S3P and X, where S2 and S3P are RA risk-enhancing alleles and S1 and S3D are RA protective alleles of the shared epitope( 1 ). Results: 109 incident RA patients from Denmark and 114 incident RA patients from Turkey were enrolled. Genetic data were available from 87% of the patients. We found no associations between the risk-enhancing alleles and the presence of IgM rheumatoid factor or ACPA. Conclusion: The Turkish patients were younger and had lower disease activity than Danish at the time of diagnosis. Our study found an enhanced genetic susceptibility to RA in Danish compared to Turkish patients with a higher prevalence of risk-enhancing RA alleles and a lower prevalence of protective alleles. References: [1]Tezenas du Montcel S, Michou L, Petit-Teixeira E, Osorio J, Lemaire I, Lasbleiz S, et al. New classification of HLA–DRB1 alleles supports the shared epitope hypothesis of rheumatoid arthritis susceptibility. Arthritis Rheum 2005; 52: 1063–8. Disclosure of Interests: None declared